Clinically Unsuspected Invasive Fungal Infections in the Setting of Malignancy. (11th September 2019) - Hendrix, Joshua; Prochilo, Gina; Serei, Virian; Brister, Kathriel; Fyfe, Billie; Minerowicz, Christine
Abstract: Background: Hospital autopsy rates are currently less than 5% of all nonmedicolegal deaths, significantly decreased from a peak of 40% to 60% in the 1960s. Studies repeatedly demonstrate that advanced imaging and laboratory tests cannot substitute for postmortem examination. We present three cases of clinically unsuspected invasive fungal infections in the setting of malignancy. Methods and Materials: We performed clinical chart reviews, postmortem examination with microbiology cultures and special stains, and literature review of three adult autopsy cases. Results: Case 1: 55-year-old man with multiple myeloma 4 days after autologous stem cell transplant who presented with rapidly deteriorating clinical status despite successful treatment for MRSA sepsis; autopsy confirmed cause of death as disseminated Rhizopus infection. Case 2: 65-year-old woman with myelodysplastic syndrome with myeloproliferative overlap and neutropenic fever on antimicrobial prophylaxis, including fluconazole. Cause of fever was presumed to be noninfectious etiology; autopsy confirmed cause of death as disseminated Candida krusei, an opportunistic invasive fungus resistant to fluconazole. Case 3: 28-year-old woman with metastatic high-grade pancreatic neuroendocrine carcinoma. An autopsy was performed for the purposes of tissue retrieval; postmortem examination demonstrated a primary pancreatic head mass with oligometastasis to the liver and disseminated Aspergillus infection. Discussion: Studies show discordance between the clinical cause of death suggested by the primary care team and the autopsy findings in up to 19% of cases. Additionally, autopsy confirmed the clinical diagnosis only 29% of the time and found that nearly 5% of antemortem diagnoses were completely refuted. Fungal infections are a frequent cause of missed diagnoses. A multi-institutional study examining 192, 095 autopsies reported a 9% prevalence of fungal infections contributing to death, half of which were missed clinically. The most common risk factor was leukemia and the most common pathogen was Aspergillus species.